Immersive virtual reality applications for design reviews: Systematic literature review and classification scheme for functionalities. (October 2022) - Horvat, Nikola; Kunnen, Steffen; Štorga, Mario; Nagarajah, Arun; Škec, Stanko
Abstract: The development of immersive virtual reality (IVR) applications for design reviews is a major trend in the design field. While many different applications have been developed, there is little consensus on the functionalities necessary for these applications. This paper proposes a classification scheme for IVR functionalities related to design reviews (DRs), combining conceptual-to-empirical and empirical-to-conceptual strategies. The classification scheme consists of eight class categories (Input, Representation, Navigation, Manipulation, Collaboration, Edit, Creation, and Output), 22 class subcategories, and 55 classes. The classification scheme has been validated by analysing several commercial IVR applications for DRs. As part of the classification scheme development, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was utilised to review 70 articles that develop IVR applications for DRs. The results from systematic literature reviews suggest the development of solutions that integrate several class categories, are better connected to current design workflows, include various design information, support a DR planning cycle, and support distributed work. The proposed classification scheme helps to orient the future development of IVR applications for DRs and provides a framework to systematically accumulate evidence on the effect of such applications on DRs.